Henticity in the drawings of the baghdad groop for modern art - عبد الأمير عبد الحسين م. د. عبد الحمزة (lark, 2019)
The current research (originality in the drawings of the Baghdad Modern Art Group) includes four chapters, the first chapter of which deals with the methodological framework of the research. It also included the importance of the research and the need for it as well as the goal of the research, which represents the following: The time limits of the research from 1951 to 1973. Spatial and Iraq, the objectivity is a group illustrations cartoons Baghdad group for modern art obtained by the researcher through books, magazines and the Internet. The second chapter includes two topics within the theoretical framework as well as previous studies. The third chapter included the research procedures by identifying the research community and its sample. Chapter three included a presentation of the results. 1 - Authenticity is clearly realized in the drawings of the Baghdad Group for Modern Art, but it is relative and not absolute 2 - achieved authenticity by a high level of form and content (expression) of the work of art, but the impact of artists Western methods led to a relative decline to achieve at the technical and stylistic level. The main conclusions include: 1- Authenticity in the drawings of the Baghdad group is an originality with a different meaning than others can be called the deep originality as it was mixed with the deep cultural heritage of the civilization of Iraq. the fourth chapter contains a set of proposals and recommendations.